Contornos de um sistema de proteção dos trabalhadores em plataformas digitais - Araújo, Aparecida Caroline Leão de (2023)
In a context of transformations of consumption patterns, means of production and raw materials, in which a new form of capitalism is consolidated by the use of modern technologies, which challenges us with a true disruption of the concepts constructed by traditional law, it is necessary to develop studies that understand the dynamics of work and the role of Labor Law. Starting from the premise that Labor Law, seen under the constitutional theme of Social Law, has as a fundamental assumption the insertion of the worker in the capitalist economy, aiming to improve his social and economic condition, it is intended to answer whether the current tools of Labor Law protect workers who perform their activities through platforms. To this end, the characteristics of these forms of work are investigated, combining literature review and analysis of the main judicial decisions of the Brazilian and international labor courts that deal with the subject, produced until the moment of the research, identifying the arguments that subsidize autonomy or subordination in digital work, as well as models that it proposes, such as the economically dependent autonomous work of Spain, the creation of a third way of protection, that would enable better regulation of the new forms of work that are found in a grise zone. We identified that there is a regulatory dilemma of these labor relations, which present a certain autonomy, but which are still subject to strong interference in the way work is carried out, through digital technologies, which belong to platform companies. In this sense, we conclude the research proposing a rereading of Labor Law, discussing the need for its interpretative expansion, no longer protecting only the subordinate worker, strengthening and reformulating the union entities, thus allowing the emergence of a more specific standardization, which could reach the most diverse labor relations, even the work developed in the digital capitalism of platforms